Remote sensing for underwater archaeology: case stud-ies from Greece and Eastern Mediterranean - Papatheodorou, G.; Geraga, M.; Chalari, A.; Christodoulou, D.; Iatrou, M.; Fakiris, E.; Kordella, St.; Prevenios, M.; Ferentinos, G. (Bulletin of the Geological Society of Greece, 2011)
Modern underwater remote sensing technology introduces many advantages that extend the range of conventional diving work providing the means to survey in a detailed and systematic fashion large seafloor area. There are two general approaches regarding the application of these techniques in underwater archaeology; they are being increasingly used to identify, locate and map (i) ancient and historical shipwrecks lying on the seafloor or partly buried in it and (ii) the coastal palaeogeogra-phy and thus submerged sites of archaeological interest (submerged ancient cities, settlements, ports and man-made structures). The underwater remote sensing techniques most commonly applied to underwater archaeology employ: (i) single and multi-beam echosounders (ii) side scan sonar (acousting imaging), (iii) laser line scan (optical imaging) (iv) subbottom profiler, (v) marine magne-tometer and (vi) undersea vehicles. The objectives of this paper are twofold: (i) to present the results of remote sensing surveys that carried out at sites of archaeological and historical interest, in Greece (Dokos Island, ancient harbour of Kyllene and Navarino Bay whereas a historical naval Battle took place) and in Eastern Mediterranean Sea (Alexandria Egypt and Mazotos shipwreck Cyprus), and (ii) to prove the applicability of remote sensing techniques in underwater archaeology showing that a combination of these can be a very effective tool.